Variance Index Score (Vis) Evaluation Of Homemade And Commercial Control Sera On Ast And Alt Assays - Rahmania, Adelia Prisma; Handayati, Anik; Museyaroh, Museyaroh; Haryanto, Edy (Poltekkes Kemenkes Semarang, 2024)
Control materials are used as indicators of monitoring the performance of laboratory examinations so that the results issued are valid. Method of assessing the implementation of External Quality Assurance (EQAS) used Variance Index Score (VIS). This study aims to determine difference between pooled sera, homemade and commercial lyophilizates on AST and ALT parameters based on VIS. This research used comparative descriptive with quantitative approach in December 2023-May 2024. Homemade lyophilizates performed at UBAYA technobiology laboratory, determination of true value performed at 2 reference laboratories and clinical chemistry laboratory Poltekkes Surabaya, and determination of VIS performed at 10 primary level clinical laboratories in Surabaya Raya which determined by purposive sampling. The statistical analysis results showed no difference between homemade and commercial control materials based on VIS to the true value and all participating laboratories, so it was concluded that homemade control materials could be used as a substitute in implementing EQAS.